TINJAUAN PADA PT. SWAKARSA TERHADAP PELAKSANAAN PEMOTONGAN, PENYETORAN, PELAPORAN DAN PENCATATAN AKUNTANSI PAJAK PPH 21 ATAS GAJI KARYAWAN TETAP - Putri Meilani Pasaribu; Rutman Lumbantoruan; Suzanna Josephine (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Taxes are one source of state revenue that is expected to reduce the dependence of our country on foreign debt. Tax sector is considered the right choice because the amount is relatively stable and the public can actively participate in development financing. Besides, to increase state revenue, the tax also aims to foster and nurture the awareness and responsibility of the State. One of the contributing factors in the national income that is derived from taxes, where the role of government is needed in order to achieve the expected national income.Proceeds from the tax sector today has become the backbone of the state revenue in the budget revenue and expenditure (APBN). PT. Swakarsa which is subject to tax that have obligations under its taxation in this case the tax cuts 21 on the income of employees covered by PT Swakarsa To determine the amount of income tax Income Tax Article 21 which must be paid it helps authors perform calculations regarding the amount of income tax Article 21 for employee salaries remain unpaid for each month. The results of the practice of field work undertaken is the calculation, remittance, reporting has been done properly in accordance with the laws OF no.36 year 2008 on the Fourth Amendment of Law Number 7 of 1983 On Income Tax. And cutting the income tax on salaries of permanent employees who have PT. Swakarsa done in accordance with the PER-31/PJ/2012. Recording for income tax accounting is in compliance with article 21 of the existing financial accounting standards.Keywords: Tax Accounting, State Revenue, Tax Article 21